Early introduction of Campus for XII grade Students to Maximize Standards Graduates Competency on Public Senior High School 1 Semarang - Dewi, Sri Purnama; Haryono, Haryono; Utanto, Yuli (Universitas Negeri Semarang, 2018)
Public Senior High School 1 Semarang is a favorite High School in Semarang City, Central Java. One of the ideal schools that is the further goal study for graduates of Junior High School in Semarang even from outside Semarang. One reason is this school is known to be successful in developing the academic and non-academic potential of students. Having students with academic abilities above average and diverse talents, the target of obtaining achievements is no longer oriented to the high value of national examinations but rather how many graduates can be accepted into college. This study aims to describe an innovative curriculum work plan related to further study programs as the development of graduate competency standards. This qualitative research uses a case study approach by analyzing the data in the form of detailed descriptions of the campus early recognition program through various data sources. Data sources were obtained from interviews, observations, and documents. The results showed that the early world recognition program had a positive impact on XII grade because they had the understanding and insight related to knick-knacks for college entrance competition by measuring their ability to compete in a university and can make a choice of majors according to their passion. The successful of this program shows that the government's effort to authorize the Education Unit to develop the Curriculum 2013 into a School Curriculum is an appropriate policy especially in developing Standards Graduates Competency for of the Education Unit Level.